2000
DOI: 10.1080/07408170008967469
|View full text |Cite
|
Sign up to set email alerts
|

General control charts for attributes

Abstract: Traditional Shewhart-type control charts ignore the skewness of the plotted statistic. Omsionally, the skewness is too large to be ignored, and in such cases the classical Shewhart chart ceases to deliver satisfactory performance. In this paper, we develop a general framework for constructing Shewhart-like control charts for attributes based on fitting a quantile function that preserves all first three moments of the plotted statistic. Furthermore, these moments enter explicitly into the formulae for calculati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 15 publications
1
22
0
Order By: Relevance
“…By adding a simple constant term to both control limits, these limits now reflect the actual skewness of the monitoring statistic (Y ), with much improved average run length properties, as previously demonstrated 10 . Furthermore, certain attributes distributions, with skewness that does not allow application of the traditional Shewhart chart, may now be also included in this modified Shewhart chart (refer to Shore 10 for details).…”
Section: Non-normality In Attributes Datamentioning
confidence: 72%
See 2 more Smart Citations
“…By adding a simple constant term to both control limits, these limits now reflect the actual skewness of the monitoring statistic (Y ), with much improved average run length properties, as previously demonstrated 10 . Furthermore, certain attributes distributions, with skewness that does not allow application of the traditional Shewhart chart, may now be also included in this modified Shewhart chart (refer to Shore 10 for details).…”
Section: Non-normality In Attributes Datamentioning
confidence: 72%
“…Various solutions attempted to remedy this shortcoming of the Shewhart chart by suggesting alternative charts with non-symmetrical control limits. A review of some of these solutions is given in Woodall 9 and in Shore 10 . However, as indicated in the latter reference, with these solutions the actual skewness of the monitoring statistic (as measured by the third standardized moment) rarely enter in the calculation of the control limits, neither is it explicitly preserved in the approximating distribution used to determine the control limits.…”
Section: Non-normality In Quality and Reliability Engineering-a Discumentioning
confidence: 98%
See 1 more Smart Citation
“…A common practice is to use the Box-Cox transformation for continuous variables and various dedicated transformations for attributes data. Examples of the latter are the arcsin transformation for binomial data or the square root transformation for Poisson data (a recent review of these transformations and others may be found in Shore 3 ). Alternatively, we may opt for the use of GLM.…”
Section: Introductionmentioning
confidence: 98%
“…Shore [2] developed control chart for random queue length, N of M /M /1queueing model by considering the first three moments. Khaparde and Dhabe [3] constructed the control chart using method of weighted variance for random queue length N for M/M/1queueing model.…”
Section: Introductionmentioning
confidence: 99%